(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Collaborative care in dentistry is paramount for achieving optimal patient outcomes, wherein dental doctors, lab technicians, and assistants synergistically contribute to comprehensive oral health care delivery. This article elucidates the intricate dynamics of teamwork within dental practices, emphasizing the pivotal roles of each profession in patient success. Dental doctors diagnose and treat oral health issues, develop personalized treatment plans, and execute procedures with precision. Lab technicians fabricate custom dental prosthetics, ensuring accuracy and functionality. Dental assistants provide chair-side support, maintain sterilization protocols, and educated patients. Through coordinated collaboration, these professionals deliver high-quality care, promoting oral health and enhancing patient well-being.